Open sun drying of green bean: influence of pretreatments on drying kinetics, colour and rehydration capacity - Ismail, Osman; Figen, Aysel Kanturk; Piskin, Sabriye (SPRINGER, 2017)
Green bean (Phaseolus Vulgaris L), classified under legume family, is a primary source of dietary protein in human diets especially in the agricultural countries. Green bean is susceptible to rapid deterioration because of their high moisture content and in order to prevent and present the green bean drying process is applied. In this study, effects of pretreatments on drying kinetics, colour and rehydration capacity of green bean were investigated. It was observed that the pretreatment affected the drying time. The shortest drying times were obtained from pretreated samples with blanched. Drying times were determined as 47, 41 and 29 h for natural, salted and blanch, respectively. The results showed that pretreatment and ambient temperature significantly (P = 0.05) affected the drying rate and the drying time. The effective moisture diffusivity was determined by using Fick's second law and was found to be range between 3.15 x 10(-10) and 1.2 x 10(-10) m(2)/s for the pre-treated and natural green bean samples. The rehydration values were obtained 2.75, 2.71, 2.29 (g water/g dry matter) for the blanched, salted and natural samples. The effective diffusion coefficients were calculated using the data collected during the falling rate period and the experimental data are fitted to seven thin layer drying models which found in the literature. The Logarithmic model was found to best describe the drying behavior of fresh green beans under open air sun. Rehydration time and color parameters had been determined in order to improve the quality of dried green bean. Regarding with rehydration time and colour data, the best results were obtained at blanched drying conditions.
Keywords: SOLAR DRYER; MINT LEAVES; LAYER; SLICES; MODEL; L.; CONVECTION; BEHAVIOR; VACUUM; RICE; Thermodynamics; Mechanics